Japanese Rinzai Zen Buddhism: Myōshinji, a living religion - Borup, Jørn (Studies in the history of religions, 2008)
Zen Buddhist ideas and practices in many ways are unique within the study of religion, and artists, poets and Buddhists practitioners worldwide have found inspiration from this tradition. This work gives a fresh perspective on contemporary Japanese Zen Buddhism